Roles of small GTPase Rac1 in the regulation of actin cytoskeleton during dengue virus infection. - Jia-Li Wang; Jun-Lei Zhang; Wei Chen; Xiao-Feng Xu; Na Gao; Dong-Ying Fan; Jing An (Public Library of Science (PLoS), 2010)
BACKGROUND: Increased vascular permeability is a hallmark feature in severe dengue virus (DV) infection, and dysfunction of endothelial cells has been speculated to contribute in the pathogenesis of dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Rho-family GTPase Rac1 is a significant element of endothelial barrier function regulation and has been implicated in the regulation of actin remodeling and intercellular junction formation. Yet there is little evidence linking Rac1 GTPase to alteration in endothelial cell function induced by DV infection. METHODS AND FINDINGS: Here, we showed that actin is essential for DV serotype 2 (DV2) entry into and release from ECV304 cells, and Rac1 signaling is involved these processes. At early infection, actin cytoskeleton rearranged significantly during 1 hour post infection, and disrupting actin filament dynamics with jasplakinolide or cytochalasin D reduced DV2 entry. DV2 entry induced reduction of Rac1 activity within 1 hour post infection. The expression of dominant-negative forms of Rac1 established that DV2 entry is negatively regulated by Rac1. At late infection, actin drugs also inhibited the DV2 release and induced accumulation of viral proteins in the cytoplasm. Meanwhile, the activity of Rac1 increased significantly with the progression of DV2 infection and was up-regulated in transfected cells expressing E protein. Confocal microscopy showed that DV2 E protein was closely associated with either actin or Rac1 in DV2-infected cells. The interaction between E protein and actin was further confirmed by co-immunoprecipitation assay. CONCLUSIONS: These results defined roles for actin integrity in DV2 entry and release, and indicated evidence for the participation of Rac1 signaling pathways in DV2-induced actin reorganizations and E-actin interaction. Our results may provide further insight into the pathogenesis of DHF/DSS.